Einblicke : Das 20. Jahrhundert in der Kunstsammlung Nordrhein-Westfalen, Düsseldorf. - Essers, Volkmar; Heinrich, Claudia; Kruszynski, Anette; Krystof, Doris; Liegl-Raditschnigg, Gudrun; Müller, Maria; Müller-Tamm, Pia; Spieler, Reinhard; Zweite, Armin (Ostfildern-Ruit : Hatje Cantz Verlag, 2000)
Albers, Josef ; Andre, Carl ; Antes, Horst ; Arakawa, Shusaku ; Arman ; Arp, Hans (Jean) ; Bacon, Francis ; Baertling, Olle ; Baselitz, Georg ; Baumeister, Willi ; Bazaine, Jean ; Becher, Bernd & Hilla ; Beckmann, Max ; Beuys, Joseph ; Bissier, Julius ; Bonnard, Pierre ; Bontecou, Lee ; Braque, Georges ; Broodthaers, Marcel ; Buchheister, Carl ; Burri, Alberto ; Caro, Anthony ; Carrà, Carlo ; Chagall, Marc ; Chamberlain, John ; Clemente, Francesco ; Dali, Salvador ; Darboven, Hanne ; De Chirico, Giorgio ; Delaunay, Robert ; Derain, André ; Dix, Otto ; Dubuffet, Jean ; Duchamp, Marcel ; Ernst, Max ; Feininger, Lyonel ; Fontana, Lucio ; Francis, Sam ; Fruhtrunk, Günter ; Giacometti, Alberto ; Goller, Bruno ; Graubner, Gotthard ; Gris, Juan ; Grosz, George ; Hartung, Hans ; Johns, Jasper ; Judd, Donald ; Kandinsky, Wassily ; Kelly, Ellsworth ; Kirchner, Ernst Ludwig ; Kirkeby, Per ; Klapheck, Konrad ; Klee, Paul ; Klein, Yves ; Kline, Franz ; Knoebel, Imi ; Kokoschka, Oskar ; Lassnig, Maria ; LeWitt, Sol ; Leger, Fernand ; Lichtenstein, Roy ; Lindner, Richard ; Lissitzky, El ; Louis, Morris ; Lüpertz, Markus ; Macke, August ; Magritte, René ; Man Ray ; Manessier, Alfred ; Manzoni, Piero ; Marc, Franz ; Matisse, Henri ; Miro, Joan ; Modigliani, Amedeo ; Mondriaan, Piet ; Morandi, Giorgio ; Morris, Robert ; Nay, Ernst Wilhelm ; Newman, Barnett ; Nicholson, Ben ; Nitsch, Hermann ; Noland, Kenneth ; Nolde, Emil ; Oelze, Richard ; Picasso, Pablo ; Pollock, Jackson ; Rainer, Arnulf ; Rauschenberg, Robert ; Richter, Gerhard ; Rothko, Mark ; Rouault, Georges ; Ruff, Thomas ; Schlemmer, Oskar ; Schnabel, Julian ; Schultze, Bernard ; Schumacher, Emil ; Schwitters, Kurt ; Scully, Sean ; Serra, Richard ; Sieverding, Katharina ; Sonderborg, K.R.H. ; Soulages, Pierre ; etc.
biog., bibliog. p. 321-731
Duits
boek